To what extent can a serious game elicit and evaluate nursing knowledge - Impey, Sinead (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2023)
This research explores to what extent a serious game could elicit and evaluate specialist nursing knowledge. The problem addressed is that not all nursing knowledge is captured in a way that is easy to access outside the border of a community of practice (CoP) or beyond geography or time. The research adopted an elaborated action design approach (eADR) by Mullarkey and Hevner (2019). This four-stage approach - diagnosis, design, implementation, and evolution - combines action research and design science research. Five interlinked contributions arise from this research. These relate to design, design knowledge or relating to theory. The design contributions are: (1) a low-fidelity serious knowledge elicitation and evaluation game artefact called The Nurses Knowledge Bank and (2) an adult oncology daycare nursing discharge reference set Ireland (SNOMED CT refset ID 134791000220109). Learning identified through the research process was embedded into the artefacts produced and formalised into design knowledge contributions. These design knowledge contributions are (1) a set of problem statements (linked to the serious game artefact) and (2) a process for mapping evaluated knowledge to clinical terminology (linked to the data reference set artefact). Lessons learned relating to the artefact could be managed through the eADR activities, cycles and stages, and then embedding lessons that emerged into the artefacts created. This thesis introduced an additional eADR stage (Reflections upon eADR) and intervention activity (end-stage reflection) as a fifth contribution.
APPROVED
Keywords: Serious games; Knowledge managment; Nursing